Effect insufficient of magnesium on quality of life in young patients with undifferentiated connective tissue dysplasia - N. Yu. Tikhomirova; L. N. Eliseeva; Z. A. Baste; I. G. Malkhasyan (Кубанский научный медицинский вестник, 2014)
Surveyed 29 people aged 20-25 years, 19 of which have a insufficient of magnesium, osteoarticular symptoms undifferentiated dysplasia оf connective tissue, who have been diagnosed with insufficient of magnesium and 10 practically healthy persons. All surveyed were divided into 2 groups: the first group consisted of 19 people, and the second 10. Evaluation of quality of life (QOL) and its comparison groups. The marked decline in the quality of life in the group 1 compared to group 2 on a range of indicators (role functioning, pain, general health, vitality, physical health component).